"I Feared for My Life": Law Enforcement's Appeal to Murderous Empathy. (April 2019) - Pipkins, Martel A.
This article utilizes critical discourse analysis (CDA) to examine discursive strategies used by police officers for justification and appeals for empathy for the murders of unarmed civilians, primarily Black civilians, while also reinforcing the implicit bias that Black individuals are dangerous. These discursive strategies show the emergence of a master narrative that connects the officers' discursive strategies for invoking empathy to avoiding blame. An analytical framework for blame avoidance supplements the CDA to underline the relationship between the master narrative and blame avoidance. Using high-profile cases in news media, I demonstrate how these narratives take various forms and work to the benefit of the officer(s) involved.